Recommendation of Marketing Mix Model for Bandung-Soekarno Hatta Railway Route (The Indonesian Journal of Business Administration, 2012)
Bandung is a city that appeals to new comers and tourists. Every week around 100.000 vehicles enter Bandung city. The tourism sector is one sector that potential to be developed in Bandung. Most of the international and domestic flights were serving by Soekarno Hatta airport in Jakarta. Therefore, the rate of transportation user- Soekarno-Hatta- Bandung increased every year. Opportunities were used by service provider such as public bus transport and travel providers. This article is trying to determine the possibility of Bandung- Soekarno Hatta’s airport railway route. The analysis conducted internal, external factors and SERVQUAL analysis in order to know PT.KAI’s performance as railway operator. The SERVQUAL analysis shows there was gap between the expectations of passenger with their expectations. The results of each attribute states that the passenger was not satisfied. This research would give a proposed solution related to the marketing mix strategy with proposed concept model line service; which includes organization, service program and maintenance. The concept model line service started with strong independent organization and follows with comprehensive service program and completed with maintenance system to achieve sustainable profitable service. Competition with other modes from ground and air make PT. KAI must improve their competence in the service of long-distance route. To be succeeding, the implementation of the model should improve on the railway service on applying on time principle, departure time corresponding with the flight schedule at Soekarno Hatta airport, communication and promotion of the channel was unknown to the public.Key Words: Rail transport, passenger, SERVQUAL, Bandung, Soekarno Hatta’s airport, Marketing Communication, Marketing Strategy.